Home advantage in Gaelic football: the effect of divisional status, season and team ability. (2nd November 2018) - Rooney, Lee; Kennedy, Rodney
ABSTRACT: Evidence suggests that home advantage (HA) is present when home teams win over 50% of home games played. This study investigated the effect of divisional status, season and team ability on HA within Gealic football. The sample included 1973 matches from 32 teams over a 9-season period. HA was calculated based on the number of points gained at home conveyed as a percentage of total points gained (Pollard and Pollard, 2005). A linear regression analysis was utilised to control for ability by adjusting HA (Pollard and Gómez, 2007). In this study, HA (57.4%) is present and significantly greater ( P < 0.001) than the null value of 50%. HA within Gaelic football is comparable to other team-based sports. Despite a decline with the last decade, HA has stabilised and remains above the proposed 50%. Team ability would appear to have a significant influence ( P < 0.05) on HA, while season and divisional status does not. Future research should investigate further causes of HA (i.e. crowd, travel and familiarity) including their impact (if any) on HA within Gaelic games.